Improving the Arabic Language Competence of Madin Teachers in Purwojati District Using the Ta'riji Method - Sudiro; Liddini, Laily (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The Arabic competence of students in Indonesia is in the low category. The low proficiency in Arabic is due to various reasons, especially because the process of learning Arabic in Indonesia only focuses on certain competencies, not comprehensively. The Ta'riji method seeks to introduce a more comprehensive Arabic learning method and improve all aspects of Arabic language skills. Various discussions used in this method can be practically applied in everyday life. This method was introduced and taught to Madrasah Diniyah teachers in Purwojati District, Banyumas Regency. As a result, there was an increase in the Arabic language skills of students taught by madrasah diniyah teachers who had attended intensive Ta'riji Method training.